Hierarchical magnetic-dielectric synergistic Co/CoO/RGO microspheres with excellent microwave absorption performance covering the whole X band. (5th January 2023) - Li, Qingqing; Tan, Jun; Wu, Zhengchen; Wang, Lei; You, Wenbin; Wu, Limin; Che, Renchao
Abstract: Based on the rational component regulation and micro-nano structure design, hierarchical dielectric-magnetic microspheres become the ideal functional materials in the microwave absorption field. Herein, unique three-dimension (3D) Co/CoO/reduced graphene oxide (RGO) (denoted as CCOR) microspheres with the hierarchical structure are prepared by a simple solvothermal method and annealing treatment. Due to the plentiful growth sites on the surface of graphene oxide, Co/CoO nanoparticles (NPs) homogeneously anchor on the RGO. Meanwhile, larger size Co/CoO particles connect 2D RGO nanosheets to form the hierarchical CCOR microspheres, which introduce abundant heterojunctions and interfaces. The electromagnetic parameters have been effectively adjusted by tuning the synergistic effect between the magnetic Co/CoO particles and highly conductive RGO nanosheets. The obtained CCOR composites exhibit excellent microwave absorption performance with the maximum reflection loss (RLmax ) of −50.1 dB. The effective absorption bandwidth reaches 6.56 GHz covering the whole X-band frequency. The outstanding microwave absorption performance of CCOR microspheres stems from the followings: i) well micro-nano structure design provides abundant heterojunction interfaces, resulting in the enhanced interfacial polarization; ii) the magnetic-dielectric synergistic loss ability from rational Co/CoO and RGO component design, facilitating the microwave energy dissipation; iii) the Co/CoO particles induce multi-scale magnetic coupling effect and strengthen the magnetic response capability. Thus, as-synthesized Co/CoO/RGO microspheres demonstrate the huge potential for application of stealth in X band as microwave absorption materials. Graphical abstract: The three-dimension (3D) hierarchical core-shell Co/CoO@Co/CoO/RGO microspheres with novel conductive network exhibited excellent magnetic-dielectric synergistic effect, strong reflection loss and ultrabroad bandwidth covering the whole X-band. Image 1 Highlights: Unique three-dimension Co/CoO/RGO microspheres with the hierarchical structure are obtained by simple method. Abundant interfacial polarization and multi-scale magnetic coupling effect contribute to the magnetic-dielectric synergy. The MA properties can be easily tuned just by tailoring the input amount of GO.